The Role of Corporate Governance in Creating a Capable Supply Chain: A Case of Indonesian Tin Industry - Petcharaporn Chatchawanchanchanakij; Chanapong Arpornpisal; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The prime objective of the current study to examine the role of corporate governance in determine the supply chain capability. The study is interested din knowing the direct impact of supply chain information technology capability, supply chain relational capability and corporate governance on the supply chain operational performance of Indonesian manufacturing firms operating in Tin industry. In addition to that we have also examined the moderating role of corporate governance in the relationship between supply chain capabilities and supply chain operational performance. To achieve the unique objectives of the current study, the authors have employed the SEM-PLS technique. The findings of the current study have provided support to with the proposed. The results have shown that the along with customer focus approach the firms are also following the production focus approach. The findings pf the study will be helpful for policy makers in understanding the issues related to corporate governance supply chain management. In author knower this is among few pioneering studies on these issues.